First Metatarsophalangeal Joint Arthrodesis - Paola Filomeno MD, MSc; Julio López MD (Foot & Ankle Orthopaedics, 2018)
Background: First metatarsophalangeal (MTP) joint arthrodesis can be fixed using either a dorsal plate or crossed screws. However, there is considerable difference in the cost of these implants, and it is not known if there is sufficient difference in outcome that might justify this cost difference. Our aim was to compare the functional results and patient satisfaction rates after first MTP joint arthrodesis in a group of patients using the same surgical technique except for the fixation devices. Methods: A prospective cohort of 27 patients who underwent first MTP joint fusion by the same surgeon using 2 crossed screws or a single screw with a dorsal plate was recruited over a 3-year period. Demographic information, patient satisfaction rates, complications, and union rates were evaluated. American Orthopaedic Foot & Ankle Society (AOFAS) and visual analog scale (VAS) scoring systems were used pre- and postoperatively to compare the functional outcomes. Thirty consecutive procedures (screws, n = 15; plate, n = 15) were performed. Age (55.8 ± 11.1 vs 63.3 ± 12.4 years for screws and plate respectively; P = .091) and female gender percentages (80% and 73%, P = .666) were similar between groups. Results: The overall union rate was 93% with no differences between groups. AOFAS and VAS scores improved significantly postoperatively for each technique, and no differences were found between the two in the improvement in AOFAS (42.4 ± 8.0 vs 44.3 ± 8.2, screws and plate respectively; P = .520) and VAS scores (66.0 ± 5.4 vs 69.0 ± 6.9; P = .195). The implant cost for screws was $40 and for dorsal plate, $328. Conclusions: First MTP joint fusion using either screws or plate fixation results in an improvement in AOFAS and VAS scores. Functional improvement and patient satisfaction did not differ between the 2 techniques, despite a considerable difference in cost between the two methods of fixation. Level of Evidence: Level III, prospective comparative study.